Examining the infectious aetiology and diagnostic criteria of maternal pyrexia in labour to improve antibiotic stewardship. (January 2019) - Fitzgerald, David J.; Knowles, Susan J.; Downey, Paul; Robson, Michael S.
Abstract: Objectives: To determine the infectious aetiology of peripartum maternal pyrexia and to assess the diagnostic accuracy of obstetric systemic inflammatory response syndrome criteria and cardiotocography as predictors of peripartum infection, in order to guide appropriate antibiotic management of mother and neonate. Study Design: This study was carried out in a tertiary referral maternity hospital in Dublin, Ireland. A prospective cohort analysis was performed of 175 mother-newborn pairs with maternal pyrexia (≥38 °C) that developed after labour onset or within four hours postnatal. Infection was confirmed microbiologically in the case of sterile site infection, urinary tract infection (UTI) or growth of a significant perinatal pathogen from a placental swab. Infection was confirmed histologically by gross and microscopic examination of placentas in cases where there was growth of potentially pathogenic micro-organisms at a non-sterile site. Systemic inflammatory response syndrome criteria and cardiotocography in patients with confirmed infection versus those without evidence of infection were compared using independent samples t-test for continuous data and pearson chi-square test for nominal data. Diagnostic accuracy of obstetric systemic inflammatory response syndrome criteria (elevated maternal heart rate, elevated respiratory rate, decreased systolic blood pressure and elevated white cell count) for the identification of infection among women with peripartum pyrexia was determined using receiver operating characteristic curves. Results: The infection rate was 17.1% (30/175). The rate was 22% (22/100) for pyrexia that occurred during labour and 10.7% (8/75) if it occurred within four hours after delivery. Obstetric systemic inflammatory response syndrome criteria and cardiotocography were not predictive of infection in women with peripartum pyrexia. No significant differences were observed in mean temperature, heart rate, respiratory rate, systolic blood pressure or white cell count between those with infections and those with no evidence of infection. Conclusions: Peripartum pyrexia is predominantly of non-infectious origin. Improved diagnostic criteria are needed to identify infection for this indication. Early discontinuation of antibiotic treatment is appropriate in the majority of patients who develop term peripartum pyrexia after onset of labour.